Praktik Sewa Perlengkapan Pernikahan di Wedding Organizer "Mutiara Cinta" Surabaya Perspektif Ijarah - Nabilah, Aghnia Faza (Maliyah : Jurnal Hukum Bisnis Islam, 2023)
This research aims to answer problems regarding the practice of renting wedding equipment at Mutiara Cinta Wedding Organizer Benowo Krajan Surabaya, as well as Ijarah analysis of this practice. This research is classified as field research conducted in Benowo Krajan Village, Surabaya. Research data was collected using interview, observation and documentation techniques. The research results concluded that the rental practice carried out by Mutiara Cinta Wedding Organizer can be done online or offline by determining the type of wedding equipment you want to rent and accompanied by a rental price agreed upon by both parties. In practice, obstacles in the field must be addressed, such as incomplete rental objects, inappropriate or defective decorations size and shape, and delayed payment deadlines. Second, renting wedding equipment at Mutiara Cinta Wedding Organizer has fulfilled the pillars and requirements of the ijarah contract, so the rental practice carried out is legal and follows Islamic law. Even though there are several obstacles in the rental course, both parties have mutually agreed and are willing to change and postpone the payment of wages according to the agreement. Thus, renting wedding equipment at Mutiara Cinta Wedding Organizer Benowo Krajan Surabaya is by and in line with Islamic law.